Analisis Efektivitas Penerapan Metode Ceramah Sebagai Strategi Pembelajaran - Harahap, Intan Insyani; Albina, Meyniar (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2025)
One of the most widely used teaching methods in the teaching and learning process is lecture, which is carried out by providing subject matter to students in an expressive or exclusive manner to achieve perfect learning objectives. In this day and age, the selection of learning strategies is more modern, learning strategies are combined with the use of technology so that they are more sophisticated and interesting. In this study, the author wants to analyze how effective the lecture method can be applied, whether it is still effective and efficient as it used to be or vice versa. Researchers use direct interview methods to get more accurate and relevant information about how effective the cerama method is as a learning strategy.